Retention of Candida Species on Plastic and Bamboo Toothbrushes. A Comparative Study - A R Avaneethram; Faizal C Peedikayil; T P Chandru; Soni Kottayi; T P Aparna; Shabnam Ismail (Wolters Kluwer Medknow Publications, 2021)
Background: Tooth brushing is the basic mode of oral hygiene practice. Various studies have shown that microorganisms can colonize on the tooth brush heads. Newer tooth brushes which are biodegradable are available in the market. This study compares the fungal colonization of plastic brush head and bamboo brush head. Materials and Methods: Fifty patients were randomly allocated into two groups with 25 each in both groups. Group 1 was given toothbrush with plastic brush head and group 2 was given toothbrushes with bamboo head. After 30 days, toothbrushes were collected. The bristles of the brush was removed from its base and put on to the petri dishes with sabouraud dextrose agar and, incubated at 28°C, with chloramphenicol and cycloheximide for 5 days. After growth was identified, pure colonies were transferred on Chromagar for the identification of Candida species. Results: Fungal growth was observed in 48% of plastic brush heads and 76% in bamboo brush heads. Candida Albicans was the most common species isolated from both plastic and bamboo tooth brushes, followed by Candida tropicalis. C. Albicans were seen as light green-colored smooth colonies; Candida tropicalis appeared as metallic blue-colored raised colonies. Candida tropicalis, Candida glabrata, Candida krusei and Candida guilliermondii were also observed. Conclusion: Fungal growth was more in bamboo tooth brushes than in plastic tooth brush even though it is statistically insignificant C. albicans is most predominant species found in the tooth brush head.